Empirical Analysis of Potato Production: in the Case of Samarkand Region, Uzbekistan (American Journal of Economics and Business Innovation, 2025)
In this research work, an economic assessment of the state of potato cultivation by farms and the factors affecting it was given in order to ensure the food security of the population. The analysis was based on the results of a social survey conducted in the farms of districts where potatoes are grown a lot in Samarkand region, using the OLS (Method of Least Squares) model. According to the results of the analysis, it was found that the age of the farm manager (*** p